2001
DOI: 10.1002/1520-636x(2001)13:2<75::aid-chir1001>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Chiral resolution and molecular modeling investigation ofrac-2-cyclopentylthio-6-[1-(2,6-difluorophenyl)ethyl]-3,4-dihydro-5-methylpyrimidin-4(3H)-one (MC-1047), a potent anti-HIV-1 reverse transcriptase agent of the DABO class

Abstract: rac-2-Cyclopentylthio-6-[1-(2,6-difluorophenyl)ethyl]-3,4-dihydro-5-methylpyrimidin-4(3H)-one (MC-1047) is a potent inhibitor of HIV-1 multiplication in acutely infected cells. MC-1047 racemate has been resolved by chiral HPLC using, as chiral stationary phase (CSP), a commercially available (R,R)-Whelk-01 column. The optical purity and the circular dichroism (CD) of the two resolved enantiomers were determined and their biological activities tested in in vitro assays. Molecular modeling inspection of the bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 15 publications
(16 reference statements)
3
39
0
Order By: Relevance
“…5-Substituted uracil analogs have been investigated extensively for use in cancer 1,2 and viral chemotherapy, 3,4 as enzyme inhibitors [5][6][7][8] and in the synthesis of modified nucleotides. 9,10 In addition, pyrimidines substituted at position C-6, as for example, 1-[(2-hydroxyethyl)-methyl]-6-(phenylthio)thymine (HEPT) 11,12 or 3,4-dihydro-2-alkoxy-6-benzyl-4-oxopyrimidines (DABOs) 13 and their derivatives [14][15][16] exhibited a potent and selective activity against human immunodeficiency virus type-1 (HIV-1). Although these compounds are relatively simple from a structural point of view, they have been the subject of great deal of chemical work.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…5-Substituted uracil analogs have been investigated extensively for use in cancer 1,2 and viral chemotherapy, 3,4 as enzyme inhibitors [5][6][7][8] and in the synthesis of modified nucleotides. 9,10 In addition, pyrimidines substituted at position C-6, as for example, 1-[(2-hydroxyethyl)-methyl]-6-(phenylthio)thymine (HEPT) 11,12 or 3,4-dihydro-2-alkoxy-6-benzyl-4-oxopyrimidines (DABOs) 13 and their derivatives [14][15][16] exhibited a potent and selective activity against human immunodeficiency virus type-1 (HIV-1). Although these compounds are relatively simple from a structural point of view, they have been the subject of great deal of chemical work.…”
Section: Introductionmentioning
confidence: 99%
“…25 Therefore, biological activities by both 5-substituted and 6-substituted uracil derivatives encouraged us to explore chemistry and biological activities of novel 5,6-disubstituted uracil derivatives. In this paper we present syntheses, X-ray crystal structural study and cytostatic evaluations of pyrimidine derivatives (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) bearing substituents at positions C-5 and C-6 of pyrimidine ring (Figure 1). a-(1-Carbamyliminomethylene)-c-butyrolactone (2) was prepared by condensation of a-acetyl-c-butyrolactone (1) with urea in ethanol.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also found that the maximal antiviral activity in the above series of compounds is intrinsic to derivatives with R configuration of the benzylic carbon atom [5]. Up to now, the only procedure reported for the preparation of optically pure 2-(cyclopentylsulfanyl)-6-[(1R)-1-(2,6-difluorophenyl)ethyl]-5-methylpyrimidin-4(3H)-one is resolution by preparative chiral chromatography [5]. There are no published data on stereoselective synthesis of this compound.…”
mentioning
confidence: 99%